1981
DOI: 10.1017/s0140525x00007330
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric laterality in animals and the effects of early experience

Abstract: A review of research with chicks, songbirds, rodents, and nonhuman primates indicates that the brain is lateralized for a number of behavioral functions. These findings can be understood in terms of three hypothetical brain processes derived from a brain model based on general systems theory: hemispheric activation, interhemispheric inhibition, and interhemispheric coupling.Left-hemisphere activation occurs in songbirds and nonhuman primates in response to salient auditory or visual input, or when a communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
187
3
3

Year Published

1985
1985
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 518 publications
(205 citation statements)
references
References 190 publications
(234 reference statements)
12
187
3
3
Order By: Relevance
“…Early social isolation also results in decreases in basal DA turnover, selectively within the IL cortex (Heidbreder et al, 2000). Postnatal handling stimulates the development of cerebral lateralization (Denenberg, 1981;Denenberg et al, 1986). Interestingly, postnatal handling, which increases maternal licking and grooming (Lee and Williams, 1975;Liu et al, 1997), results in significantly reduced synaptic density in the IL cortex compared with nonhandled controls (Ovtscharoff and Braun, 2001), which may in part account for the reduced anxiety and high exploration typically displayed by neonatally handled animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early social isolation also results in decreases in basal DA turnover, selectively within the IL cortex (Heidbreder et al, 2000). Postnatal handling stimulates the development of cerebral lateralization (Denenberg, 1981;Denenberg et al, 1986). Interestingly, postnatal handling, which increases maternal licking and grooming (Lee and Williams, 1975;Liu et al, 1997), results in significantly reduced synaptic density in the IL cortex compared with nonhandled controls (Ovtscharoff and Braun, 2001), which may in part account for the reduced anxiety and high exploration typically displayed by neonatally handled animals.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps less well known is that the DA inputs to the left and right mPFC are functionally asymmetric, particularly with respect to stress responsivity (Slopsema et al, 1982;Carlson et al, 1991Carlson et al, , 1993Carlson et al, , 1996Sullivan and Szechtman, 1995;Sullivan and Gratton, 1998;Andersen and Teicher, 1999;Berridge et al, 1999;Thiel and Schwarting, 2001). Furthermore, the development of such hemispheric asymmetries in mPFC function can be altered by perinatal factors and the early postnatal rearing environment (Denenberg, 1981;Denenberg et al, 1986;Brake et al, 2000). These findings along with evidence derived from clinical observations have led to the suggestion that abnormal lateralization of mPFC DA-mediated function may increase the vulnerability to a range of stress-related psychopathologies (for review, see Sullivan and Gratton, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…To successfully hatch, the posture of the chick embryo must be oriented toward the top of the egg with the right side facing outward, thus providing a greater degree of mobility to the right side of the body (Oppenheim, 1972). This, in turn, provides more sensory and motor experience to the right side of the body, which appears to facilitate the development of hemispheriC lateralization and related behavioral asymmetry (see Denenberg, 1981, for a similar argument in mammalian species).…”
Section: Discussionmentioning
confidence: 99%
“…Individual turning bias indices were computed using a typical laterality formula (see Corballis, 1991;Denenberg, 1981). The formula produces a quantitative index for the direction of turning bias: (R -L)/(R + L).…”
Section: Behavioral Measurementioning
confidence: 99%
“…Lesions studies revealed that the rat brain shows a substantial hemispheric specialization (Denenberg, 1981;Sullivan, 2004). Furthermore, PET and fMRI imaging studies in humans demonstrated unilateral activations of prefrontal subregions .…”
Section: Fdg-pet Imagingmentioning
confidence: 99%